Responding to the literacy load of science in monocultural contexts: : Preparation programs can change teacher classroom behavior - Duckworth, Brian; MacQueen , Suzanne; O'Toole, J. Mitchell (Universitas Terbuka, 2024)
Existing research about literacy within different subjects suggests that specialist language styles add an extra load to student learning. This has resulted in changes to centralized policy mandates in various jurisdictions, eliciting a variety of responses, including enthusiasm, agreement, compliance, neglect, subversion, and/or resistance. This mixed method study investigated whether 55 secondary school teachers from a culturally homogenous coastal region of Eastern Australia recognized literacy issues within science and their responses to such issues. There were three main findings. Firstly, only one third of participating mainstream science teachers accepted direct responsibility for helping their students deal with the literacy load of science, but most participating teachers recognized the literacy nature of more than half of the activities suggested to them. Secondly, participants teaching classes at several grade levels, and female participants, reported using a greater range of literacy activities in their science classes, and more clearly content-related activities were mentioned more frequently. Thirdly, participants who had completed a postgraduate teacher preparation program were more likely to express confidence in dealing with the literacy load of science and acceptance of responsibility for doing so. Time spent on literacy in teacher preparation programs appears to influence positive mainstream science teacher attitudes and practices in response to the literacy load of science. Study findings challenge conventional views of teacher recalcitrance, and they support the maintenance of policy and teacher preparation practices that encourage science teachers to respond productively to student literacy needs that have been identified by on-going research.